The truth war : fighting for certainty in an age of deception - MacArthur, John, 1939- (Nashville, Tenn. : Nelson Books, 2007)
Right now, Truth is under attack, and much is at stake. Christians are caught in the crossfire of alternative Christian histories, emerging faulty texts, and a cultural push to eliminate absolute Truth altogether. As a result, many churches and Christians have been deceived. Worse still, they propagate the deception that poses itself as Truth! In The Truth War John MacArthur reclaims the unwavering certainty of God's Truth and anchors Christians in the eternal, immovable promises that are found in His Word. - Publisher.
Introduction : why truth is worth fighting for -- Can truth survive in a postmodern society? -- Spiritual warfare : duty, danger, and guaranteed triumph -- Constrained into conflict : why we must fight for the faith -- Creeping apostasy : how false teachers sneak in -- Heresy's subtlety : why we must remain vigilant -- The evil of false teaching : how error turns grace into licentiousness -- The assault on divine authority : Christ's lordship denied -- How to survive in an age of apostasy : learning from the lessons of history -- Appendix : why discernment is out of fashion.
Includes bibliographical references (pages 216-224).
Keywords: Truth -- Religious aspects -- Christianity; Evangelicalism; Christian life